2020
DOI: 10.1002/aqc.3314
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution modelling of striped dolphin (Stenella coeruleoalba) at different geographical scales within the EU Adriatic and Ionian Sea Region, central‐eastern Mediterranean Sea

Abstract: The striped dolphin (Stenella coeruleoalba) is one of the most abundant cetaceans of the Mediterranean Sea. Nevertheless, it is ranked as ‘Vulnerable’ by IUCN Red List experts. To implement conservation strategies within the Mediterranean Sea, it is crucial to understand how striped dolphins are distributed at different geographical scales. The present study investigates its distribution within the EU Adriatic and Ionian Sea Region. To model striped dolphin distribution, topographic (distance from shore, depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Although the Gulf of Taranto is characterized by a marked anthropogenic presence and intense fishing exploitation (Carlucci et al 2016), the occurrence of cetacean species, such as the striped dolphin (Stenella coeruleoalba), the common bottlenose dolphin (Tursiops truncatus), the Risso's dolphin (Grampus griseus), the sperm whale (Physeter macrocephalus) and the fin whale (Balaenoptera physalus) makes this area eligible for the establishment of a Specially Protected Area of Mediterranean Importance (SPAMI), according to the SPA/BD Protocol (Carlucci et al 2018b, c;Maglietta et al 2018;Azzolin et al 2020). In particular, the striped and common bottlenose dolphins are the most frequent and abundant species distributed throughout the Gulf of Taranto (Carlucci et al 2016(Carlucci et al , 2018b.…”
Section: Study Areamentioning
confidence: 99%
“…Although the Gulf of Taranto is characterized by a marked anthropogenic presence and intense fishing exploitation (Carlucci et al 2016), the occurrence of cetacean species, such as the striped dolphin (Stenella coeruleoalba), the common bottlenose dolphin (Tursiops truncatus), the Risso's dolphin (Grampus griseus), the sperm whale (Physeter macrocephalus) and the fin whale (Balaenoptera physalus) makes this area eligible for the establishment of a Specially Protected Area of Mediterranean Importance (SPAMI), according to the SPA/BD Protocol (Carlucci et al 2018b, c;Maglietta et al 2018;Azzolin et al 2020). In particular, the striped and common bottlenose dolphins are the most frequent and abundant species distributed throughout the Gulf of Taranto (Carlucci et al 2016(Carlucci et al , 2018b.…”
Section: Study Areamentioning
confidence: 99%
“…A narrow continental shelf with a steep slope and several channels characterizes the western sector, while the eastern sector shows descending terraces toward the "Taranto Valley, " a NW-SE submarine canyon with no clear bathymetric connection to a major river system (Capezzuto et al, 2010;Russo et al, 2017;Carlucci et al, 2018a). The striped dolphin regularly occurs in the northernmost portion of the Taranto Valley (Azzolin et al, 2020), most likely attracted by the high productivity of the sub-marine canyon system and its upwelling currents (Carlucci et al, 2018c).…”
Section: Study Areamentioning
confidence: 99%
“…The use of ferries as platforms for conducting dedicated research has been increasing in recent years. It has been demonstrated that data collection following specific protocols can result in the successful use of the data for species distribution studies ( Kiszka et al, 2007 ; Arcangeli, Marini & Crosti, 2012 ; Aïssi et al, 2015 ; Correia et al, 2015 ; Morgado et al, 2017 ; Azzolin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%